To Save or Save Not: Intergenerational Neutrality and the Expansion of New Zealand Superannuation - Andrew Coleman (New Zealand Government, The Treasury, 2014)
Increases in longevity mean the size of New Zealand's public retirement income programme, New Zealand Superannuation, will automatically expand unless the age of eligibility is increased. This paper analyses the consequences of expanding New Zealand Superannuation on a save-as-you-go basis through the New Zealand Superannuation Fund rather than on a pay-as-you-go basis. These funding mechanisms differ in terms of their effects on different cohorts, on long run tax rates, on capital accumulation, and on risk. The paper argues that an automatic pay-as-you-go funded expansion of New Zealand Superannuation is unattractive on many grounds, even if pay-as-you-go funding remains for much of the programme. In addition to reducing long run tax rates, the use of save-as-you-go funding through the New Zealand Superannuation Fund provides households with a means of reducing income risk over the course of their lives.
Keywords: E21; H55; 330; Retirement income policy; prefunding; intergenerational economics; Gesetzliche Rentenversicherung; Umlageverfahren; Kapitaldeckungsverfahren; Altersvorsorge; Neuseeland